Phase development during thermal treatment of a fast-setting cordierite-mullite refractory - Hipedinger, Nora Elba (2015)
Cordierite based materials are widely used in high temperature applications due to their good thermo-mechanical properties and thermal shock resistance. They are generally employed in the kiln furniture (shelves, brackets, bearing plates) for firing ceramic pieces. Because of its low expansion coefficient and dielectric properties, cordierite is also used in advanced ceramics, catalyst supports automotive, industrial waste gas purification and parts subjected to sudden temperature changes. The low intrinsic strength of the cordierite may be compensated by the presence of mullite, forming a composite material of cordierite-mullite, extending its use to somewhat higher temperatures, at the expense of a slight increase in the thermal expansion coefficient. In this work a cordierite-mullite precursor was prepared from a mixture of magnesium oxide, calcined alumina, silica fume and monoaluminum phosphate solution that produces fast setting at room temperature (~20 minutes) and then, by calcination, cordierite-mullite is generated. The evolution of the mineralogical phases was studied from room temperature to 1350 °C by Xray diffraction, differential thermal analysis and thermogravimetry. A possible sequence of chemicals reactions throughout the heat treatment is also proposed. Adding refractory aggregates to this precursor leads to obtaining a fast-setting concrete, suitable for the formation of individual pieces or repair service at moderately high temperatures. A summary of its main properties is also included.